The Influence of Prices, Income, E-Cigarettes, and Social Environments on Cigarette Consumption Behavior of Teenagers - Fadillah, Aris; Asna Prestianawati, Silvi (Journal of Development Economic and Social Studies, 2025)
This study aims to analyze the influence of cigarette price increases, income, e-cigarettes, and social environment on the smoking behavior of teenage smokers of machine-made clove cigarettes (SKM). The background of this research is driven by the high rate of cigarette consumption among teenagers, despite the continuous increase in cigarette prices and the emergence of alternative products such as e-cigarettes. This research uses a quantitative method with a survey approach involving active teenage smokers as respondents. The sampling technique used is purposive sampling, and the data were analyzed using multiple linear regression with SPSS software. The results show that variables cigarette price, income, e-cigarettes, and social environment also has a significant influence. These findings indicate that teenage smoking behavior is influenced not only by economic factors but also by social factors and the availability of substitute products.